CESER: An R Package to Compute Cluster Estimated Standard Errors. (30th November 2021) - Ferrari, Diogo
This paper presents an implementation in R of the Cluster Estimated Standard Errors (CESE) proposed by [12 ]. The method estimates the covariance matrix of the estimated coefficients of linear models in grouped data sets with correlation among observations within groups. Cluster Estimated Standard Errors (CESE) is an alternative solution for the classical Cluster Robust Standard Errors (CRSE) [8 13 15 ], which underestimates the standard errors in most of the situations encountered in practice [7 ].